The discrepancy between manual and computerized leukocyte and thrombocyte counts - Bambang Permono; Retno Asih; I Dewa Gede Ugrasena (Paediatrica Indonesiana, 2003)
Background Discrepancy between results of leukocyte and throm-bocyte count by computerized and manual examination may existObjective To determine the discrepancy between computerizedand manual leukocyte and thrombocyte count.Methods The design was a randomized sampling cross sectionalstudy. The blood sample was examined with computerized CellDyn 1400 instrument for the leukocyte and thrombocyte count. Formanual examination, blood smear was performed to measurethrombocyte while leukocyte was measured in Improved Neubauerhemocytometer. The results of computerized examination wereused as gold standard. Sensitivity, specificity, predictive values ofmanual count were calculated. The agreement of Kappa and McNemar test were determinedResults Blood specimens drawn from 100 patients with differentkinds of diagnoses were examined using computerized and manualmethods. In computerized group, 66% had normal leukocyte and55% had normal thrombocyte count. In the manual group, 78% ofsubjects had normal leukocyte and 82% had normal thrombocytecount. From leukocyte examination, the sensitivity of manual countwas 87.9%, specificity was 41.2%, and positive predictive valuewas 74.36 with the agreement of Kappa of 0.32 and Mc Nemarvalue of 0.036. From thrombocyte examination, the sensitivity was96.4%, specificity was 35.6%, and positive predictive value was64.6 with the agreement of Kappa of 0.41 and Mc Nemar value of0.41.Conclusion The result of manual thrombocyte count was in ac-cordance with computerized with the agreement of Kappa of 0.41.On the other hand, there was a discrepancy between manual infavor of computerized leukocyte count with the agreement of Kappaof 0.32